Positive Semiotics. Issue 3 (September 2019) - Lomas, Tim
Although semiotics has historically been a focus of interest in psychology, its impact over recent decades has been fairly muted. Moreover, no systematic efforts have been made to study and understand it from a positive perspective, that is, the way sign-systems are or can be "positive." As such, this article introduces the notion of "positive semiotics, " a label for the disparate research and theorizing that is already underway across academia relating to this topic. The article draws on the work of Charles Sanders Peirce, particularly in terms of his triadic view of sign-systems as comprising a sign, an object, and an interpretant. The idea of positivity is then elucidated using the criterion of desirability, drawing on the work of James Pawelski. Attempts are also made to ascertain the nature of desirability, including normative forms (clarified here using the conceptual triad of goodness, truth, and beauty) and nonnormative forms (understood as personal wants). The article then considers four key semiotic channels—discursive language, body language, symbols, and art—looking at selective examples of how positive semiotics might pertain to that channel. It is hoped the article will stimulate further interest in, and work on, a phenomenon that is of considerable importance to psychology and beyond.